The strategy of composite grafting with BMP2-Loaded calcium phosphate cements and autogenous bone for alveolar cleft reconstruction - Shen, Hongzhou; Li, Lvyuan; Zhang, Chenglong; Chen, Yang; Yu, Hongbo; Si, Jiawen; Shen, Guofang (Frontiers in Physiology, 2022)
Purpose: To remedy the drawbacks of traditional autogenous bone harvesting in alveolar bone grafting (ABG), a novel strategy of composite grafting with BMP2-loaded calcium phosphate cements (BMP2-CPC) and autogenous bone harvested by minimally invasive technique was developed and evaluated for its bone-repairing efficacy. Materials and methods: A chart review was conducted for 19 patients with unilateral alveolar clefts who underwent secondary ABG from 2017 to 2020. Of the enrolled patients, 9 patients underwent grafting with autogenous bone harvested by traditional trap door technique (group I), and 10 patients underwent grafting with the composite graft comprising BMP2-CPC and autogenous bone harvested by minimally invasive technique at a ratio of 1:1 by volume (group II). The clinical performance of the composite graft was comprehensively evaluated in terms of clinical, radiographic and histological perspectives. Results: The present results demonstrated that the composite graft exhibited satisfactory bone-repairing efficacy comparable to that of the autogenous bone graft on the premise of lower amount of harvested bone. The post-surgical resorption of bone volume and vertical height of grafted area was significantly slower in group II. The favourable resorption performance of BMP2-CPC contributed to preserving the post-surgical bony contour reconstructed with the composite graft. Conclusion: The composite graft comprising BMP2-CPC and autogenous bone harvested by minimally invasive technique was demonstrated to be an eligible alternative for application in ABG, especially for its improved resorption performance in preserving post-surgical bony contour.